The art of hegel's aesthetics: hegelian philosophy and the perspectives of art history - Kottman, Paul A.; Squire, Michael (Wilhelm Fink, 2018)
This volume explores Hegel’s 1820s »Vorlesungen über die Ästhetik«. The objective is two-fold: first, to ask how Hegel’s work might illuminate specific periods and artworks in light of contemporary art historical discussions; and second, to explore how art history might help us to make better sense (and use) of Hegelian aesthetics. Given the recent resurgence of interest in ›global‹ art history, and calls for more comparative approaches to »visual culture«, the volume asks what role Hegel has played or could play within the field. What can a historical treatment of art accomplish? How should we explain the »need« for certain artistic forms at different historical junctures? Has art history been »Hegelian« without fully acknowledging the fact? Indeed, in what ways have art historians shirked the fundamental questions that Hegel raised?
Keywords: Aufsatzsammlung; Konferenzschrift -- 2016 -- London; Ästhetik; Hegel, Georg Wilhelm Friedrich